2016
DOI: 10.1038/ncomms12348
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous wound healing through paradoxical MAPK activation by BRAF inhibitors

Abstract: BRAF inhibitors are highly effective therapies for the treatment of BRAFV600-mutated melanoma, with the main toxicity being a variety of hyperproliferative skin conditions due to paradoxical activation of the mitogen-activated protein kinase (MAPK) pathway in BRAF wild-type cells. Most of these hyperproliferative skin changes improve when a MEK inhibitor is co-administered, as it blocks paradoxical MAPK activation. Here we show how the BRAF inhibitor vemurafenib accelerates skin wound healing by inducing the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 25 publications
5
63
0
1
Order By: Relevance
“…Specifically, transcriptome analysis of AMG-treated fibroblasts clearly showed upregulation of the MAPK/ERK-signaling pathway, suggesting its involvement in the AMG molecular mechanism. It has been previously shown that activation of the ERK signaling cascade is positively involved in WH mainly through its capacity to stimulate cell proliferation (15). On the other hand, recent evidences show the role of the MAPK pathway in the enhancement of cell migration and morphology, angiogenesis (30) and, most importantly, in regulating tissue repair functions in fibroblasts (31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, transcriptome analysis of AMG-treated fibroblasts clearly showed upregulation of the MAPK/ERK-signaling pathway, suggesting its involvement in the AMG molecular mechanism. It has been previously shown that activation of the ERK signaling cascade is positively involved in WH mainly through its capacity to stimulate cell proliferation (15). On the other hand, recent evidences show the role of the MAPK pathway in the enhancement of cell migration and morphology, angiogenesis (30) and, most importantly, in regulating tissue repair functions in fibroblasts (31).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the strong AMG treatment ability to promote motility and migration of fibroblasts in vitro, we used the excisional WH mouse model to address whether topical application of AMG would also stimulate the healing capacity of full-thickness dermal wounds in vivo. In parallel, we tested the involvement of the MAPK cascade on in vivo AMG treatment by using the specific MEK inhibitor trametinib (15).…”
Section: Erk Signaling Pathway Drives Autologous Micrograft-mediated Whmentioning
confidence: 99%
See 1 more Smart Citation
“…BRAF inhibitors enhance patient survival, but also stimulate metastasis through ERK/ MAPK activation in RAS mutant melanoma cells [188]. This same drug-induced MAPK activation improves wound healing in mouse models by stimulating keratinocyte hyperproliferation [189].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 97%
“…Our group has shown that the topical application of an EGFR inhibitor can enhance the immune response to cutaneous vaccination . More recently, the topical application of the BRAF V600E ‐selective inhibitor vemurafenib has shown promise as a treatment to accelerate wound healing through its paradoxical ability to activate the MAPK pathway . Thus, in addition to their use as systemic agents, locally applied targeted therapies may harbor potential for the treatment of diseases affecting accessible epithelial tissues.…”
Section: Local Application Of Targeted Therapiesmentioning
confidence: 99%